Endoscopic ultrasound guided biliary drainage: a multicenter retrospective experience of a technique slowly gaining acceptance in Egypt - Altonbary, Ahmed Youssef (Ther Adv Gastrointest Endosc, 2019)
BACKGROUND AND AIM: Endoscopic ultrasound-guided biliary drainage is an alternative to failed endoscopic retrograde cholangiopancreatography. Unfortunately, this procedure remains relatively less explored in Egypt due to its high cost, lack of adequate training, and the perception of increased risk. This study is the first multicenter Egyptian experience of an endoscopic ultrasound-guided biliary drainage in patients with malignant biliary obstruction. PATIENTS AND METHODS: We retrospectively reviewed 15 patients (10 men and five women) with malignant biliary obstruction who from October 2013 to May 2019, following a failed or inaccessible endoscopic retrograde cholangiopancreatography, underwent an endoscopic ultrasound-guided choledochoduodenostomy, endoscopic ultrasound-guided hepaticogastrostomy, or endoscopic ultrasound-guided rendezvous. Their mean age was 57.4 years and mean bilirubin was 18.2 mg/dL. The outcome parameters included technical and clinical success. Technical success was defined as the successful placement of a stent in the biliary system, while clinical success was defined as a greater than 50% decrease in the bilirubin levels 2 weeks after the procedure. Patients were monitored for complications during and after the procedure. RESULTS: In total, 15 patients underwent endoscopic ultrasound-guided biliary drainage (eight underwent endoscopic ultrasound-guided choledochoduodenostomy, five underwent endoscopic ultrasound-guided hepaticogastrostomy, and two underwent endoscopic ultrasound-guided rendezvous). The technical and clinical success rates were 100% (15/15 patients) and 93.3% (14/15 patients), respectively. The complication rate was 26.6% (4/15 patients). All complications were mild and self-limited, and included fever, mild biliary peritonitis, pneumoperitoneum, and a slight migration of one plastic stent during insertion. CONCLUSION: Although slowly gaining acceptance in Egypt, endoscopic ultrasound-guided biliary drainage is an effective and safe procedure in patients with a malignant biliary obstruction after a failed or inaccessible endoscopic retrograde cholangiopancreatography.